PENGARUH LAYANAN PENGUASAAN KONTEN TERHADAP KREATIVITAS BELAJAR SISWA KELAS XI SMA NEGERI 3 SUSUA - Ndruru, Agusria (Universitas Nias Raya, 2024)
This study is based on the fact that many students still do not have curiosity, students do not have self-confidence, students are not independent in learning, students still do not dare to express their opinions, students do not dare to try something new. This study aims to determine the learning creativity of class XI students of SMA Negeri 3 Susua before being given content mastery services. To determine the learning creativity of class XI students of SMA Negeri 3 Susua after being given content mastery services. To determine the effect of content mastery services on student learning creativity. The type of research is quantitative with a quasi-experimental method. The population of the study was students of SMA Negeri 3 Susua while the sample was class XI of SMA Negeri 3 Susua totaling 28 students. The data of this study were analyzed using normality tests and hypothesis tests using the SPSS (statistical product and service solution) version 20 application. The results of this study are the sig. (2-tailed) value of 0.015 <0.05, it is known that t count 2.59601> t table 0.381. The conclusion is that students have creativity in learning and have self-confidence. Suggestions, 1) for teachers, to be able to develop content mastery services for students' learning creativity in carrying out variations in the learning process. 2) for researchers, this study can add insight and new knowledge about the influence of content mastery services on students' learning creativity in grade XI of SMA Negeri 3 Susua. 3) for further researchers, this study can be an additional reference in conducting relevant research. 4) for Nias Raya University, this study can be a collection in the library as well as a reference for students who want to make relevant research with a wider scope.